Contours of Sexuality in Roy’s The God of Small Things - Shrivastwa, Bimal Kishore (KMC Journal, 2024)
This study aims at analyzing the contours of sexuality, obscenity and incest in Arundhati Roy’s debut novel, The God of Small Things to mark how the novelist deconstructs the naturalized and normalized social, ethical, and cultural values in the Indian society. The illicit relationship between the central character of the novel and a divorced woman, Ammu and the servant of her family, Velutha, the incest between Estha and Rahel, an incident where an old man forces Estha to masturbate, and the sensual affair of Baby Kochamma with Father Mulligan are some of the highly charged obscene details in the novel that invite a keen rationale for the research. The research utilizes the theoretical framework of psychoanalysis and radical feminism that deal with sexuality, feminine sexuality, and sibling incest to observe Roy’s motive for emphasizing on pornographic drives. Both Freudian psychoanalysts and radical feminists deal with the sex overtly taking it as the basic human instinct. The research finding is that Roy emphasizes the graphic description of sexual acts among members of family and different castes to cherish beauty found in ‘small things’, to mystify the mundane, to examine the issues of unethical sex in revolutionary South-Asian societies. It is expected that people interested in researching libidinal issues in Roy in particular, and South-Asian literature in general, can take the paper as a reference.